2019
DOI: 10.1111/ijd.14374
|View full text |Cite
|
Sign up to set email alerts
|

Mohs micrographic surgery versus wide local excision for melanoma in situ: analysis of a nationwide database

Abstract: Background With the rising incidence of melanoma in situ (MIS) or cutaneous melanoma, there is an increasing emphasis on the need to understand optimal treatment strategies. The current standard of surgical care is wide local excision (WLE). Alternative surgical techniques have been proposed including Mohs micrographic surgery (MMS). We aimed to compare survival rates following WLE versus MMS surgery for MIS. Methods We performed a retrospective analysis of the Surveillance, Epidemiology, and End Results (SEER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Compared to WLE, MMS offers the possibility of total margin evaluation and has been associated with decreased rates of recurrence [ 33 ]. Other recent studies contradict these findings by suggesting no differences in overall survival, cancer-specific survival, and recurrence rates amongst patients treated with MMS and WLE [ 29 , 39 ]. There is a misconception that MMS is more costly than WLE, but recent preliminary work [ 34 ] would imply that MMS is more cost-effective than WLE, particularly with an increased incidence of skin cancers [ 1 ].…”
Section: Discussionmentioning
confidence: 97%
“…Compared to WLE, MMS offers the possibility of total margin evaluation and has been associated with decreased rates of recurrence [ 33 ]. Other recent studies contradict these findings by suggesting no differences in overall survival, cancer-specific survival, and recurrence rates amongst patients treated with MMS and WLE [ 29 , 39 ]. There is a misconception that MMS is more costly than WLE, but recent preliminary work [ 34 ] would imply that MMS is more cost-effective than WLE, particularly with an increased incidence of skin cancers [ 1 ].…”
Section: Discussionmentioning
confidence: 97%
“…It is in cases of melanoma in situ, and in particular lentigo maligna, where MMS can be a very powerful technique in clearing the disease and obtaining very low local recurrence rates 4 . However, some retrospective institutional and database studies have found no difference in local control rates or overall survival in melanoma in situ patients treated with MMS versus WLE 23,24 . It is likely that both MMS and WLE are effective treatment options for most CMHN, with MMS outperforming WLE in cases of subclinical spread beyond the visible borders of the lesion.…”
Section: Discussionmentioning
confidence: 99%
“…A metastasectomy is recommended for patients with metastatic melanoma by the National Comprehensive Cancer Network guidelines 18 ; however, the guidelines lack proper descriptions regarding whether primary tumor resections should be routinely practiced in advanced melanoma patients or not, and the conclusions are limited by conditions such as solitary lesions. Selection bias may be contributing to observed associations between survival benefit and surgery in previous retrospective studies 6,8,11,19,20 .…”
Section: Discussionmentioning
confidence: 99%